Plasma 25-hydroxyvitamin D concentration and subsequent risk of total and site specific cancers in Japanese population: large case-cohort study within Japan Public Health Center-based Prospective Study cohort. (7th March 2018) - Budhathoki, Sanjeev; Hidaka, Akihisa; Yamaji, Taiki; Sawada, Norie; Tanaka-Mizuno, Sachiko; Kuchiba, Aya; Charvat, Hadrien; Goto, Atsushi; Kojima, Satoshi; Sudo, Natsuki; Shimazu, Taichi; Sasazuki, Shizuka; et al.
Abstract: Objective: To evaluate the association between pre-diagnostic circulating vitamin D concentration and the subsequent risk of overall and site specific cancer in a large cohort study. Design: Nested case-cohort study within the Japan Public Health Center-based Prospective Study cohort. Setting: Nine public health centre areas across Japan. Participants: 3301 incident cases of cancer and 4044 randomly selected subcohort participants. Exposure: Plasma concentration of 25-hydroxyvitamin D measured by enzyme immunoassay. Participants were divided into quarters based on the sex and season specific distribution of 25-hydroxyvitamin D among subcohorts. Weighted Cox proportional hazard models were used to calculate the multivariable adjusted hazard ratios for overall and site specific cancer across categories of 25-hydroxyvitamin D concentration, with the lowest quarter as the reference. Main outcome measure: Incidence of overall or site specific cancer. Results: Plasma 25-hydroxyvitamin D concentration was inversely associated with the risk of total cancer, with multivariable adjusted hazard ratios for the second to fourth quarters compared with the lowest quarter of 0.81 (95% confidence interval 0.70 to 0.94), 0.75 (0.65 to 0.87), and 0.78 (0.67 to 0.91), respectively (P for trend=0.001). Among the findings for cancers at specific sites, an inverse association was found for liver cancer, with corresponding hazard ratios of 0.70 (0.44 to 1.13), 0.65 (0.40 to 1.06), and 0.45 (0.26 to 0.79) (P for trend=0.006). A sensitivity analysis showed that alternately removing cases of cancer at one specific site from total cancer cases did not substantially change the overall hazard ratios. Conclusions: In this large prospective study, higher vitamin D concentration was associated with lower risk of total cancer. These findings support the hypothesis that vitamin D has protective effects against cancers at many sites.